My little pony: legends of magic (2017), volume 1 ebook Legends of magic, vol. 1. - Whitley, Jeremy (My Little Pony: Legends of Magic (2017), 2017)
The first collection of an all-new series devoted to revealing the secret history of Equestria. It's all here: the origins of cutie marks, friendships, magic, and more! In this opening story arc, we travel back in time to uncover the secrets of Starswirl the Bearded and his magical friends! Sure to entice longtime readers, it also makes a good entry point for new fans of the characters. Collects issues #1–6. Author: Jeremy Whitley. Illustrator: Brenda Hickey. © 2018 Hasbro. All Rights Reserved.